RELATIONSHIP BETWEEN STRESS WITH GASTRITIS IN THE REGION OF PUBLIC HEALTH SERVICE JATIREJO DISTRICT MOJOKERTO - RARAS MERBAWANI; MOH SAJIDIN; ASEF WILDAN MUNFADLILA (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Gastritis is one of the most common problems of the digestive tract and increases annually. Gastritis is a pain that is not caused by disorders of the stomach organs but more often triggered by psychological stress factors. Stomach acid production will increase in stressful situations, eg in heavy workloads, panic and haste. Increased stomach acid levels can irritate the gastric mucosa. The purpose of this study was to determine the relationship of stress with recurrence of gastritis in the area of ​​public health service jatirejo mojokerto . Design of an analytic survey study used a cohort design. Population was of all gastritis patients in puskesmas jatirejo mojokerto regency and get a sample of 35 people, taken with purposive sampling technique. Independent variable of stress level and dependent variable of recurrence of gastritis. The instrument used to measure stress is a questionnaire while the instrument used to measure the recurrence of gastritis is using an observation sheet. The research was conducted on 28 March-29 April. Data analysis used cross tabulation (crosstab). The results showed that most respondents had moderate stress level as many as 16 respondents and experienced recurrence as many as 13 respondents (81.2%) .This is caused by people who are vulnerable to stress, because the more vulnerable a person exposed to stress the higher the risk of gastritis